The Effect of Legal Infrastructure Construction and Environmental, Social, and Governance Disclosure on Audit Opinion - Nafiatul Fariq Putri Khosiah; Marita Kusuma Wardani (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the influence of Legal Infrastructure Construction (LIC) and Environmental, Social, and Governance Disclosure (ESGD) on audit opinions in manufacturing companies listed on the Indonesia Stock Exchange for the 2022–2024 period. This research is motivated by the increasing demands for transparency, accountability, and sustainability reporting in the business world. The study uses a quantitative approach with secondary data obtained from annual reports and company sustainability reports. The study sample consisted of 155 manufacturing companies with a total of 465 observations selected using purposive sampling. Data analysis was performed using ordinal logistic regression with the help of EViews 14. The results show that Legal Infrastructure Construction and ESG Disclosure have a positive effect on audit opinions. Companies with high levels of regulatory compliance and ESG disclosure tend to obtain better audit opinions because they are perceived to have better transparency and quality of governance. This study supports legitimacy theory and provides implications for regulators and companies in improving sustainability reporting and corporate governance practices.